2005
DOI: 10.1063/1.2064314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies of the effect of phase difference between transport current and perpendicular applied magnetic field on total ac loss in Ag-sheathed (Bi,Pb)2Sr2Ca2Cu3Ox tape

Abstract: The effect of phase difference between transport current and perpendicular applied magnetic field, Δφ, on total ac loss in multifilamentary, silver-sheathed (Bi,Pb)2Sr2Ca2Cu3Ox (Bi-2223) superconducting tapes was calculated numerically using Brandt’s equation [Phys. Rev. B 54, 4246 (1996)] and the results were compared with experimental results obtained by the calorimetric method. In the numerical calculations, the superconducting transition was modeled by E-J characteristics represented by a power law. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Latter facts agree with the analytical approaches for the slab 60 and strip 61 geometries. Also, in further agreement with the experimental evidences, [43][44][45] within our statement we predict that as long as a phase shifting occurs, at least a minimal reduction of the ac loss should be observed.…”
Section: -12supporting
confidence: 91%
See 1 more Smart Citation
“…Latter facts agree with the analytical approaches for the slab 60 and strip 61 geometries. Also, in further agreement with the experimental evidences, [43][44][45] within our statement we predict that as long as a phase shifting occurs, at least a minimal reduction of the ac loss should be observed.…”
Section: -12supporting
confidence: 91%
“…Moreover, remarkable experimental differences between the ac loss measured for superconducting wires or tapes with synchronous and asynchronous oscillating transport current and perpendicular magnetic field have been already reported by several authors. [43][44][45] In what follows we will address the effects related to the consideration of asynchronous excitations, in which, both sources may be out of phase and apply at different frequencies. However, given the enormous number of possibilities to analyze, we will focus on the influence of double frequency effects over the actual estimation of the ac losses in a superconducting wire, when any of the electromagnetic sources is plugged to some power grid with a double frequency than the other.…”
Section: Asynchronous Excitationsmentioning
confidence: 99%
“…These calculations predict that the ac loss maximum is when the alternating current and field are in phase with each other. However, simulations for slabs [139] and elliptical wires [140], [75] show that for large applied fields, the ac loss maximum is at intermediate phase shifts for both a powerlaw E(J) relation and the critical-state model. Experiments confirm this [140], [75].…”
Section: Solutions For Particular Casesmentioning
confidence: 96%
“…Previous studies based on HTS tapes showed that total AC loss of HTS tapes increased when transport current or external magnetic field was increased [25,26], and it is influenced by the phase shift between the current and the external magnetic field [14,[15][16][17][18][19]. These result indicated that the total AC loss of machine AC windings depends not only on the magnitudes of the magnetic field and transport current, but also on the interaction between the magnetic field and the current.…”
Section: Introductionmentioning
confidence: 92%